Profile of women in situation of abortion assisted in a public maternity in Teresina-PI - Ariane Gomes dos Santos; Inez Sampaio Nery; Érida Zoé Lustosa Furtado; Fernanda Maria de Jesus Sousa Pires de Moura (Rev Rene)
Abortion is a public health problem resulting from the inter-relationship between socio-economic and cultural factors, among others. The study aimed to identify the profile of women in situation of abortion assisted in a public maternity hospital in Teresina – PI – Brazil. It is a quantitative research. The data collection was conducted by the authors through the technique of interview with questionnaires to 70 women. The results showed that the prevalent age of the respondents was 20-28 years (42,9%), 35.7% with incomplete basic education, 61.4% did not perform paid work, 50.0% had family income up to the minimum wage; 34.3% had a steady relationship, 67.1% had had menarche between 12 and 14 years of age and 74.2% had their first intercourse between 15 and 19. Thus, we realized the importance of creating spaces for dialogue on domestic environment, as well as proper support and monitoring by health professionals, especially nurses, to women who had been victims of abortion.